MENINGKATKAN PENGUASAAN VOCABULARY DENGAN MEDIA FLASHCARD DI SMK AL HIKAM - Lidia Deviga (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This research aims to improve vocabulary mastery in English subjects by utilizing flashcard media for 10th-grade students at SMK AL HIKAM. The methods employed are mentoring and teaching vocabulary with the goal of developing oral language skills. The subjects of this study were 42 students of class 10 at SMK AL HIKAM, consisting of 30 female students and 12 male students. There were three flashcard techniques used in this community service activity: Flash, Slowly-Slowly, and Magic Eyes. The Flash technique requires students to guess the image shown rapidly by the researcher. The Slowly-Slowly technique involves students guessing the image as it is revealed gradually. Finally, the Magic Eyes technique involves singing lyrics composed by the researcher that correspond to the displayed flashcards. The vocabulary material taught to the 10th-grade students focused on "Daily Activities." During the activity, students showed great enthusiasm in learning English vocabulary, and there was a noticeable improvement in their mastery. It is hoped that flashcard media will continue to be implemented by teachers in the classroom teaching and learning process.